COMPREHENSIVE REHABILITATION OF TROPHIC ULCERS USING PHYSICAL FACTORS (Physical Culture and Sport: Scientific Perspective, 2025)
The article describes one of the modern approaches to solving the most widespread and often unrecognized and underestimated problems in the whole world - the problems of treating patients with varicose veins of the lower extremities, complicated by trophic ulcers. Ulcers that do not heal for a long time significantly impair a person's ability to social and professional activities, reduce the quality of life and impose financial restrictions. In this study, the feasibility and proven effectiveness of the use of physical therapy methods in the complex rehabilitation of patients with trophic ulcers of the lower extremities is substantiated, taking into account the duration of the disease, the phase of the wound process, as well as the size of the ulcer defect.The study is based on a comparative evaluation of the results of complex treatment of patients of working age. Clinical examination was carried out according to traditional rules and consisted of anamnesis collection, examination of general and local statuses. The article describes the technique and provides a comparative assessment of the use of various physical factors in the complex treatment and prevention of disease relapses, an analysis of the effectiveness of the influence of various physical factors on the course of healing processes of trophic ulcers of the lower extremities. The author demonstrated a clear advantage of the combined use of magnetotherapy and intratissue electrophoresis (magnetogalvanotherapy) in comparison with other researched methods. The expediency and effectiveness of the proposed methods, which were used in the treatment of patients with trophic ulcers of the lower extremities, is evidenced by the achievement of a high clinical effect and a reduction in the length of hospitalization.
Keywords: complex rehabilitation; trophic ulcers; physical factors; physical therapy; intratissue electrophoresis; magnetotherapy; magnetogalvanotherapy